2011
DOI: 10.1158/1078-0432.ccr-10-3152
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Loss ofmiR-486Regulates Tumor Progression and theOLFM4Antiapoptotic Factor in Gastric Cancer

Abstract: Purpose: MicroRNAs (miRNA) play pivotal oncogenic and tumor-suppressor roles in several human cancers. We sought to discover novel tumor-suppressor miRNAs in gastric cancer (GC).Experimental Design: Using Agilent miRNA microarrays, we compared miRNA expression profiles of 40 primary gastric tumors and 40 gastric normal tissues, identifying miRNAs significantly downregulated in gastric tumors.Results: Among the top 80 miRNAs differentially expressed between gastric tumors and normals (false discovery rate < 0.0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
152
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(165 citation statements)
references
References 43 publications
8
152
3
Order By: Relevance
“…Thus, our results together with previous studies suggest that miR-486 plays important roles in the progression of gliomas and that miR-486 expression may be useful for evaluating responses to therapy and surveillance of cancer outcomes. Interestingly, Oh et al [46] found that miR-486 is downregulated in gastric cancer and functions as a tumor suppressor. It has been proposed that a single miRNA may have several distinct functions in different cell types, which likely depends on the availability of specific targets or downstream effectors [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our results together with previous studies suggest that miR-486 plays important roles in the progression of gliomas and that miR-486 expression may be useful for evaluating responses to therapy and surveillance of cancer outcomes. Interestingly, Oh et al [46] found that miR-486 is downregulated in gastric cancer and functions as a tumor suppressor. It has been proposed that a single miRNA may have several distinct functions in different cell types, which likely depends on the availability of specific targets or downstream effectors [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated that miRNA expression is associated with cell proliferation, metastasis, invasion and and response to therapy (14)(15)(16)(17)(18)(19)(20). miRNA expression differs between cancer tissues and adjacent normal tissues in patients (21)(22)(23). These data indicate that miRNAs may be used as potential biomarkers for the diagnosis and prognosis of patients with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that miR-486-5p has also been found to be downregulated in numerous other cancer types, including pancreatic cancer (34), gastric cancer (29), osteosarcoma (35), and lung cancer (23), however, the mechanism of miR-486-5p downregulation in those types of cancer, including HCC, is largely unknown. According to previous studies, miR-486-5p downregulation in HCC tissues could be highly accredited to its chromosomal location (8p11.21), which is one of the most typically occurring genomic deletion regions, containing potential tumor suppressor genes (29).…”
Section: A B Discussionmentioning
confidence: 99%
“…According to previous studies, miR-486-5p downregulation in HCC tissues could be highly accredited to its chromosomal location (8p11.21), which is one of the most typically occurring genomic deletion regions, containing potential tumor suppressor genes (29). Epigenetic silencing …”
Section: A B Discussionmentioning
confidence: 99%
See 1 more Smart Citation